Cordyceps polysaccharide marker CCP modulates immune responses via highly selective TLR4/MyD88/p38 axis. (1st November 2021) - Zhang, Quanwei; Liu, Man; Li, Lifeng; Chen, Miaomiao; Puno, Pema Tenzin; Bao, Wanrong; Zheng, Hongming; Wen, Xin; Cheng, Huiyuan; Fung, Hauyee; Wong, Tinlong; Zhao, Zhongzhen; et al.
Abstract: Cordyceps, one of the most expensive natural health supplements, is popularly used to modulate immune function. However, little is known regarding the underlying mechanism of its immunomodulatory activity. We newly reported a Cordyceps quality marker CCP (Mw 433.778 kDa) which was characterized as a 1, 4-α glucan by chemical and spectral analysis and is able to induce significant immune responses of macrophages. Herein, we further investigated the molecular mechanism of CCP's immunomodulatory effects. The results indicate that CCP modulates the TLR4/MyD88/p38 signaling pathway of macrophages, where TLR4 plays a crucial role as verified on TLR4-deficient (TLR4 −/− ) bone marrow-derived macrophages (BMDMs) and TLR4 −/− mice. These findings provide a precise understanding of the molecular mechanism of Cordyceps' immunomodulatory benefits. Graphical abstract: Unlabelled Image Highlights: Cordyceps polysaccharide marker CCP modulates the immune responses of macrophage. The direct targeting receptors of CCP might be TLR4, TLR1/2 or TLR2/6. CCP's immunomodulatory effect on macrophages is MyD88/p38 dependent. TLR4 rather than TLR1/2 or TLR2/6 mediates CCP's immunomodulatory effects.